A novel vibration sensor system for frequency measurement based on Bias Flip technique. (August 2018) - Zhao, Sheng; Fu, Haipeng
Highlights: A piezoelectric energy harvesting device is used to sense ambient vibration. Bias Flip technique is used to track the ambient vibration frequency. A signal conditioning circuit is developed to measure the vibration frequency. Abstract: This paper describes a new type of vibration sensor system for the real-time measurement of vibration frequency. The proposed sensor system consists of a piezoelectric energy harvesting device and a signal conditioning circuit. The piezoelectric energy harvesting device is used to sense and convert ambient vibration to a relevant output voltage. The signal conditioning circuit, made up by a Bias-Flip circuit, a pulse shaper and a low pass filter, is employed to generate a DC output voltage which is proportional to the magnitude of the vibration frequency. The proposed vibration sensor system is successfully demonstrated through SPICE simulation. In addition, an experimental setup has been designed and fabricated to verify the proposed system. When the sinusoidal vibration excitation from 200 Hz to 500 Hz is applied to the vibration sensor system, the measurement results fit very well with the theoretical prediction. The relative error between theoretical and experimental results is less than 1.6%.